Curahan Kerja dan Kontribusi Wanita Tani Terhadap Pendapatan Rumah Tangga Petani Padi Sawah di Kota Bengkulu - Rihan Ifebri; Bembi Akbar Serawai; Hariz Eko Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2026)
This study aims to analyze the productive activities, labor time allocation, income structure, and the contribution of women rice farmers’ income to total household income in Bengkulu City. The research employed a survey method with a quantitative approach. Data were analyzed descriptively and through income contribution calculations to determine the extent of women farmers’ economic role within the household. The results indicate that the productive activities of women rice farmers include lowland rice farming, upland farming, agricultural wage labor, trading, and employment as private-sector workers. The largest allocation of time in economic activities was devoted to trading, amounting to 5.9 hours per day, while in non-economic activities most of the time was allocated to household responsibilities, also averaging 5.9 hours per day. The highest income earned by women farmers originated from the non-farm sector, particularly trading or private employment, amounting to IDR 938,330 per month, which also constituted the largest source within the overall household income structure, averaging IDR 3,383,333 per month. Nevertheless, the largest contribution to total household income derived from agricultural wage labor activities, accounting for 34.71%. These findings suggest that income diversification plays a crucial role in strengthening the economic resilience of women rice farming households